Minutes, meetings, and 'modes of existence': navigating the bureaucratic process of urban regeneration in East London. (16th March 2017) - Evans, Gillian
Abstract : Inspired by Latour's aim to restore balance to the anthropological project by exoticizing the artefacts and procedures of so‐called 'modern knowledge', this essay gives an ethnographic description of emergent processes of knowledge production in the context of the planning and development of urban regeneration in London. Bureaucratic meetings are described as part of the organizational infrastructure that enables the crafting of new urban futures, and it is argued that, because the making of reality is always seen to be forward moving, there is a need, as in navigation, to plot a course. The essay focuses on the subversive potential of informal meetings, and argues, more generally, that meetings are the materially social, and affectively technical, manoeuvres that make possible direction‐finding and contestation about the way forward.